The Effectiveness Of English Debate In Enhancing Eleventh Grade Of Students’ Speaking Skills - Safitri, Hilma; Lisahnes Suntari (Universitas Cokroaminoto Palopo, 2024)
This study aimed to investigate the effectiveness of English debate on the speaking skills of eleventh-grade students at SMA Yadika 10 Kosambi, Tangerang Regency. By employing a pre-experimental design with pre- and post-tests, the study utilized a quantitative approach to analyze data collected from student actions, verbal expressions, and supplementary written documents, pictures, or statistical data. The study's theoretical framework was grounded in Sibuea's (2021) theory of debate, which posits that engaging in debate fosters critical thinking, communication, and language development. Data analysis was conducted using SPSS 20. Descriptive statistical analysis revealed a substantial improvement in students' speaking skills. The average pre-test score was 1.18 (standard deviation 0.39), while the average post-test score was 2.32 (standard deviation 0.55). This significant increase suggested that the debate intervention positively affected students' speaking skills. Further analysis revealed a positive correlation (r = 0.425) between pre-test and post-test scores, indicating that the observed improvement was directly attributable to the intervention. A paired samples t-test confirmed this finding, revealing a mean difference of -1.14 with a t-statistic of -23.897 (p < 0.001). This highly significant difference strongly supported the conclusion that the debate method significantly enhanced students' speaking skills in terms of grammar, vocabulary, comprehension, fluency, and pronunciation. These improvements were evident in the post-test scores, demonstrating the effectiveness of English debate in fostering holistic speaking development.